Self-esteem and satisfaction with social relationships across time - De Moor, Elisabeth L.; Denissen, Jaap J. A.; Emons, Wilco H. M.; Bleidorn, Wiebke; Luhmann, Maike; Orth, Ulrich; Chung, Joanne M. (American Psychological Association, 2021)
Research on the longitudinal association between self-esteem and satisfaction with social relationships has led to ambiguous conclusions regarding the temporal order and strength of this relation. Existing studies have examined this association across intervals ranging from days to years, leaving it unclear as to what extent differences in timing may explain differences across studies. In the present study, we used continuous time structural equation models (i.e., CT-SEM) to examine cross-lagged relations between the constructs, and also distinguished between-person differences from within-person processes (i.e., RI-CT-SEM). We analyzed 10 years of annual data from the Longitudinal Internet Studies of the Social Sciences (N = 14,741). When using CT-SEM, we found a bidirectional positive relation between self-esteem and satisfaction with social relationships, with larger effects over longer intervals. When using RI-CT-SEM, we found the largest effects of self-esteem and satisfaction with social relationships across intervals of 1 year, with smaller effect sizes at both shorter and longer intervals. In addition, the effect of fluctuations in people's satisfaction with social relationships on fluctuations in their self-esteem was greater than the reverse effect. Our results highlight the importance of considering time when examining the relation between self-esteem and interpersonal outcomes and likely psychological constructs in general. (PsycInfo Database Record (c) 2021 APA, all rights reserved)
Keywords: continuous time modeling; cross-lagged panel model; random-intercept cross-lagged panel model; relationship satisfaction; self-esteem; Taverne; Social Psychology; Sociology and Political Science